2
$\begingroup$

Let $X(t) = \int_{-\infty}^{\infty} h(u) Y(t-u)du $ be a process where $Y(t)$ is stationary with mean $0$. I want to calculate the mean and the autocovariance function of $X(t)$. So:

$$ E(X(t)) = \int_{-\infty}^{\infty} \int_{-\infty}^{\infty} h(u) Y(t-u)du f_Y(t) dt $$

I know the answer must be zero. My question is: can I invert the integrals and compute it? Meaning:

$$ E(X(t)) = \int_{-\infty}^{\infty} h(u) \int_{-\infty}^{\infty} Y(t-u)f_Y(t) dt du =0 $$

Thanks!

======

Edit.

======

For the autocovariance function:

$$ E(X(t) X(t-h)) = E\left(\int_{\mathbb{R}} h(u) Y(t-u)du \int_{\mathbb{R}} h(v) Y(t-h-v)dv \right) $$

I know the result must be $$ \gamma_X(h) =\int_{\mathbb{R}} h(u) h(v) \gamma_Y(h+v-u) du dv $$ but I still can't figure why the expected value resulted in the above equation. For me it would be the same with:

$$ \gamma_Y(h+v+u) $$

Thanks!

$\endgroup$
2
$\begingroup$

Making this calculation is conceptually difficult to do unless we are clear on what is meant by \begin{equation} \int_{\mathbb{R}} h(u)Y(t-u)\,\mathrm{d}u. \end{equation} It is a random variable and so there is the additional variable that makes it random! Thus we have \begin{equation} X(t,\omega) = \int_{\mathbb{R}} h(u)Y(t-u,\omega)\,\mathrm{d}u. \end{equation}

Deriving the expectation is then just an application of Fubini's theorem and the argument would be \begin{equation} E_{\omega}\left[\int_{\mathbb{R}} h(u)Y(t-u,\omega)\,\mathrm{d}u\right] = \int_{\mathbb{R}} h(u)E_\omega[Y(t-u,\omega)]\,\mathrm{d}u =0. \end{equation} As a rule of thumb: "the expected value of the integral is the integral of the expected value".

For the autocovariance function we can proceed similarly (note that I have dropped the "random" argument). Again we use Fubini's theorem to interchange expectation and integral, \begin{align} E(X(t)X(t-k)) &= E\left(\int_{\mathbb{R}} h(u)Y(t -u) \, \mathrm{d}u\int_{\mathbb{R}} h(v)Y(t-k-v) \, \mathrm{d}v\right) \\ &= E\left(\int_{\mathbb{R}}\int_{\mathbb{R}} h(u)h(v)Y(t -u)Y(t-k-v) \, \,\mathrm{d}u\,\mathrm{d}v\right) \\ &= \int_{\mathbb{R}}\int_{\mathbb{R}} h(u)h(v)E[Y(t -u)Y(t-k-v)] \, \,\mathrm{d}u\,\mathrm{d}v. \end{align} Using the fact that $E[Y(t -u)Y(t-k-v)] = \text{Cov}_Y(t-u,t-k-v)$ and since $Y$ is stationary, $\text{Cov}_Y(t-u,t-k-v) = \gamma_Y(t-u -(t-k-v)) = \gamma_Y(k+v-u)$. Thus, \begin{equation} \gamma_X(k) = \int_{\mathbb{R}}\int_{\mathbb{R}} h(u)h(v)\gamma_Y(k+v-u) \, \,\mathrm{d}u\,\mathrm{d}v. \end{equation}


More detail on why this is OK to do:

We have, \begin{align} E_{\omega}\left[\int_{\mathbb{R}} h(u)Y(t-u,\omega)\,\mathrm{d}u\right] &= \int_{\mathbb{R}}\int_{\mathbb{R}} h(u)Y(t-u,\omega)\,\mathrm{d}u\, f(\omega)\,\mathrm{d}\omega \\ &= \int_{\mathbb{R}} h(u)\int_{\mathbb{R}} Y(t-u,\omega)f(\omega)\,\mathrm{d}\omega\,\mathrm{d}u \\ &= \int_{\mathbb{R}} h(u) E_\omega[Y(t-u,\omega)]\,\mathrm{d}u. \end{align} Fubini's theorem is used to interchange the integral signs in the second step (given of course that the conditions of Fubini's theorem are fulfilled).

$\endgroup$
4
  • $\begingroup$ Excelent! Thank you so much! I will edit my comment as I try to evaluate the autocovariance function - and see if the answer matches. $\endgroup$ – YetAnotherUsr Sep 3 '19 at 6:09
  • $\begingroup$ I edited my question $\endgroup$ – YetAnotherUsr Sep 4 '19 at 21:53
  • $\begingroup$ @M.Gonzalez I edited my answer $\endgroup$ – Timothy Hedgeworth Sep 4 '19 at 23:10
  • $\begingroup$ Thanks, Timothy! :) $\endgroup$ – YetAnotherUsr Sep 5 '19 at 13:41

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.